The Effect Of Digital Training On Teacher Performance : The Mediating Role Of Digital Self-Efficacy Among Teachers At SMA Negeri 1 Selesai - Firmansyah Firmansyah; Siswa Pratama; Syafril Gustiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effect of Digital Training on Teacher Performance with Digital Self-Efficacy as a mediating variable. The research is based on the increasing need for teachers to adapt to digital learning environments and to improve their professional performance through technology-based competencies. A quantitative approach was employed using survey data collected from teachers and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model was evaluated through outer loading, Cronbach’s Alpha, Composite Reliability, Average Variance Extracted, Fornell-Larcker criterion, cross-loading, and HTMT, while the structural model was assessed using R-square, direct effects, and indirect effects. The results show that Digital Training has a positive and significant effect on Teacher Performance. Digital Training also has a positive and significant effect on Digital Self-Efficacy. Furthermore, Digital Self-Efficacy positively and significantly affects Teacher Performance. The mediation test confirms that Digital Self-Efficacy partially mediates the relationship between Digital Training and Teacher Performance. The model explains 54.1% of the variance in Digital Self-Efficacy and 78.3% of the variance in Teacher Performance, indicating moderate to substantial explanatory power. These findings suggest that digital training contributes not only to teachers’ technical competence but also to their confidence in using digital technologies. Therefore, educational institutions should develop continuous digital training programs supported by mentoring and practical implementation to enhance teacher performance in digital learning settings.